2018
DOI: 10.1159/000489811
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PCK1 Gene Antagonizes Hepatocellular Carcinoma Through the Activation of Gluconeogenesis and Suppression of Glycolysis Pathways

Abstract: Background/Aims: Gluconeogenesis, a reverse process of glycolysis, is suppressed in neoplastic livers. Cytoplasmic phosphoenolpyruvate carboxykinase (PEPCK-C/PCK1, encoded by PCK1) is a step limiting enzyme of gluconeogenesis. The induced expression of the factor is reported to initiate gluconeogenesis process and antagonize hepatocellular carcinoma (HCC). In the current study, the effect of the modulation of PCK1 expression on HCC was assessed. Methods: The levels of PCK1 in clinical HCC tissues and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…Glycolysis is a common way for all organisms to extract energy from glucose, and gluconeogenesis provides a source for new glucose molecules. Glucose is produced from small carbohydrate substrates such as pyruvate, lactic acid, glycerin, and glucose amino acids, and to synthesize glucose from simple starting materials to meet the needs of various tissues [26][27]. And In our study, when BSS occurred, the model group showed signi cant upregulation of pyruvate, suggesting that glucose metabolism disorders may occur.…”
Section: Discussionmentioning
confidence: 63%
“…Glycolysis is a common way for all organisms to extract energy from glucose, and gluconeogenesis provides a source for new glucose molecules. Glucose is produced from small carbohydrate substrates such as pyruvate, lactic acid, glycerin, and glucose amino acids, and to synthesize glucose from simple starting materials to meet the needs of various tissues [26][27]. And In our study, when BSS occurred, the model group showed signi cant upregulation of pyruvate, suggesting that glucose metabolism disorders may occur.…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, the PCK1 gene, which is involved in both the PPAR signaling pathway and metabolic pathway, is a main control point for the regulation of gluconeogenesis. The expression of this gene can be regulated by insulin, glucocorticoids, glucagon, cAMP, and diet and it has multiple relationships with several metabolic diseases [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis is a glucose utilization process, which converts glucose into pyruvate or lactate. Gluconeogenesis is opposite to that of glycolysis, which synthesizes glucose from other metabolites like pyruvate, lactate, and glucogenic amino acids (Tang et al, 2018). Glycolysis and gluconeogenesis possess several reversible enzyme-catalyzed reactions and share a series of common intermediates such as glucose-6-phosphate, fructose-6-phosphate, fructose-1, 6bisphosphate, lactate, etc (Sharabi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%